Virtual network functions placement in 5G architecture: a survey and a multi-agent approach. (10th March 2021) - Retal, Sara; Idrissi, Abdellah
New needs required by emerging communication obligations necessitate a fifth-generation (5G) mobile network. Indeed, the evolution of communication thanks to all connected devices made the society highly networked. Consequently, information and data must be available everywhere and every-time for everyone. 5G Mobile Network Architecture is a new framework that uses existing technologies such as cloud computing to meet the requirements of numerous applications that increase data traffic daily. In this vein, we provide a comprehensive analysis of one of the main challenges facing this architecture, which is the placement of the virtual network functions (VNFs) and emphasise its link with the cloud computing field.We also present significant works dealing with this problem, comparing them, and propose a multi-agent system approach that enhances these works.